Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445510
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and Defending Against Seizure-Inducing GIFs in Social Media

Abstract: The creator uses a risk detection system and removes the harmful sequences before releasing the animation. The user is safe.The attacker intentionally sidesteps creator-driven protections.The user is at risk! Creator-driven protection ACCIDENTAL ATTACK Consumer-driven protectionThe dangerous content is flagged and removed before it is seen by the user. The user is safe. Consumer-driven protectionThe dangerous content is flagged and removed before it is seen by the user. The user is safe.A content creator accid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Social media exposure has a positive correlation to seizure experiences. Recent research conducted by South et al [ 14 ] stated that exposure to certain visual patterns on social media could trigger seizures among 3% of individuals with epilepsy. Particularly, videos and GIFs have severe effects on people with photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Social media exposure has a positive correlation to seizure experiences. Recent research conducted by South et al [ 14 ] stated that exposure to certain visual patterns on social media could trigger seizures among 3% of individuals with epilepsy. Particularly, videos and GIFs have severe effects on people with photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on accessibility for people with photosensitive epilepsy has focused on accurate and efcient detection of seizureinducing content in videos [1,3], GIFs [16], and interactive data visualizations [15]. Conversely, this work focuses on the question of how to communicate information about photosensitive risk to the viewer after a risk detection system has already identifed the potential hazard.…”
Section: Related Work 21 Photosensitive Accessibilitymentioning
confidence: 99%
“…Conversely, this work focuses on the question of how to communicate information about photosensitive risk to the viewer after a risk detection system has already identifed the potential hazard. Prior qualitative research has shown that warnings attached to seizure-inducing content are considered useful and valuable for individuals with PSE when navigating online spaces [16]. Photosensitivity warnings are commonplace on user-generated content sites such as YouTube (Figure 1C).…”
Section: Related Work 21 Photosensitive Accessibilitymentioning
confidence: 99%
“…Strobing lights can directly trigger physical pain through visual stimulus alone. Flashing lights have induced epileptic seizures, not only in children watching television [73], but also in adults playing video games, as seen during the release of the 2 Or perhaps its opposite, apathy. 2020 game Cyberpunk 2077, which contained a sequence of flashes similar to that used by neurologists to induce seizures [16].…”
Section: Graphic Violence (Physical Direct)mentioning
confidence: 99%
“…All that is truly needed from us is a willingness to use strobing visualizations as mere cosmetic trappings, without regard for their medical ramifications for some viewers. We refer the reader to South et al [72,73], who describe a set of highly usable methods for formulating such attacks.…”
Section: Graphic Violence (Physical Direct)mentioning
confidence: 99%